Students’ (Dis)satisfaction with Synchronous Online Learning in Times of COVID-19 - Adil El Filali (The Journal of Quality in Education, 2022)
This paper measures the effects of COVID-19 on university students’ learning performance. Students’ degree of (dis)satisfaction with real-time virtual instruction is a determining factor in their achievement. This variable (students’ degree of (dis)satisfaction) may better be understood with reference to the barriers that face students regarding their synchronous virtual learning. Specifically, highlighting the impact of the pandemic on such mode of learning helps identify and explore such barriers. To this end, two crucial aspects are worthy of mention. While the first concerns the students’ degree of (did)satisfaction with the learning mode in focus, the second focuses on the difficulties who students encounter in such mode of learning. Methodologically, data was collected through an online questionnaire distributed to 101 students at the Higher School of Technology –Essaouira. The data analysis phase consists of both the students’ responses and their comments. The former is analysed quantitatively, while the latter are analysed on the basis of the themes emerging from them. The study demonstrates that most participants hold fewer positive attitudes towards real-time online courses particularly during this period of crisis. It also shows that most students encounter many difficulties while learning English synchronously, which makes them favour in-class settings over the synchronous ones. The importance of this study lies in that it helps get an insight into the students’ views of and experience with real-time online learning during COVID -19. The study, however, may call for further research associated with other issues different from the one under investigation.